2017
DOI: 10.1007/164_2016_5007
|View full text |Cite
|
Sign up to set email alerts
|

cCMP and cUMP in Apoptosis: Concepts and Methods

Abstract: The cyclic nucleotides cAMP and cGMP are well-characterized second messenger molecules regulating many important intracellular processes, such as differentiation, proliferation, and apoptosis. The latter is a highly regulated process of programmed cell death wherein several regulatory proteins, like those belonging to the Bcl-2 family, are involved. The initiation of apoptosis is regulated by three different pathways: the intrinsic or mitochondrial, the extrinsic, and the ER stress pathway. Recently, it has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Cells infected with P. aeruginosa expressing a functional T3SS have been shown to upregulate CD95/CD95L, which—upon activation—induces apoptosis [ 30 ]. In addition, it has been shown that high intracellular concentrations of cUMP can stimulate apoptosis [ 31 , 32 , 33 ]. An excessive incidence of cell death in the lung leads to a breakdown of lung barrier integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Cells infected with P. aeruginosa expressing a functional T3SS have been shown to upregulate CD95/CD95L, which—upon activation—induces apoptosis [ 30 ]. In addition, it has been shown that high intracellular concentrations of cUMP can stimulate apoptosis [ 31 , 32 , 33 ]. An excessive incidence of cell death in the lung leads to a breakdown of lung barrier integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Since the cyclic nucleotides cAMP and cGMP were wellcharacterized second messenger molecules regulating many intracellular processes, such as cell proliferation, migration (Wolter et al, 2017), we further explored whether Frontiers in Pharmacology frontiersin.org PRO20 inhibited pathological cardiac remodeling through modulating intracellular cAMP and cGMP levels. Upon Ang II stimulation in CFs and CMs, intracellular cAMP and cGMP levels were significantly decreased (Figures 5A-D).…”
Section: Pro20 Enhanced Intracellular Camp Levels and Attenuated Endo...mentioning
confidence: 99%